Perinatal and early life risk factors for childhood brain tumors: Is instrument-assisted delivery associated with higher risk?. (April 2019) - ,; Bourgioti, Charis; Dana, Helen; Papadopoulos, Savvas; Sfakianos, Georgios; Themistocleous, Marios; Stefanaki, Kalliopi; Strantzia, Katerina; Zountsas, Basilios; Vakis, Antonios; Manolitsi, Katerina; Kelekis, Nikolaos; et al.
Highlights: The brain tumor peak in childhood points to early-life exposures as potential risk factors. We explored perinatal and early-life risk factors for childhood brain tumors in a nationwide case-control study. Instrument-assisted delivery, alcohol consumption in pregnancy, and history of living in a farm were associated with higher odds of brain tumors. Higher birth order was associated with lower risk. Early-life indicators of brain trauma, toxic agent exposure, and immunity maturation might be involved in childhood brain tumor pathogenesis. Abstract: Background: The childhood peak of brain tumors suggests that early-life exposures might have a role in their etiology. Hence, we examined in the Greek National Registry for Childhood Hematological Malignancies and Solid tumors (NARECHEM-ST) whether perinatal and early-life risk factors influence the risk of childhood brain tumors. Methods: In a nationwide case-control study, we included 203 cases (0–14 years) with a diagnosis of brain tumor in NARECHEM-ST (2010–2016) and 406 age-, sex-, and center-matched hospital controls. Information was collected via interviews with the guardians and we analyzed the variables of interest in multivariable conditional logistic regression models. Results: Instrument-assisted delivery was associated with higher (OR: 7.82, 95%CI: 2.18–28.03), whereas caesarean delivery with lower (OR: 0.67, 95%CI: 0.45-0.99) risk of childhood brain tumors, as compared to spontaneous vaginal delivery. Maternal alcohol consumption during pregnancy (OR: 2.35, 95%CI: 1.45–3.81) and history of living in a farm (OR: 4.98, 2.40–10.32) increased the odds of childhood brain tumors. Conversely, higher birth order was associated with lower risk (OR for 2nd vs. 1st child: 0.60, 95%CI: 0.40-0.89 and OR for 3 rd vs. 1 st : 0.34, 95%CI: 0.18-0.63). Birth weight, gestational age, parental age, history of infertility, smoking during pregnancy, allergic diseases, and maternal diseases during pregnancy showed no significant associations. Conclusions: Perinatal and early-life risk factors, and specifically indicators of brain trauma, exposure to toxic agents and immune system maturation, might be involved in the pathogenesis of childhood brain tumors. Larger studies should aim to replicate our findings and examine associations with tumor subtypes.